KOMUNIKASI VERBAL DAN NON VERBAL DALAM JALINAN IKATAN COMMITTED RELATIONSHIP PADA PASANGAN GAY - Novi Andayani Praptiningsih (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2015)
AbstractThis study focuses on verbal and non verbalcommunication between gay couple in establishinga committed relationship. The conflict consists ofinternal conflict between the gay couple of differentnations and external conflict caused by stigm,discrimination, and bullying is done by thecommunity. This study is a qualitative study usingdata collection by conducting in-depth interviewsand observations of three gay couples. The resultsshowed that gay couples have a specific strategy inmaintaining a relationship commitment thatreflected through their verbal or nonverbalcommunication that is tailored to the character oftheir relationship. Emotional attachment that isgoing on between the two gay couples could also bea reason for them to maintain their intimacyrelationship. Conflict experienced by gay couples,because of jealousy, possessive and aggressiveattitudes that dominate one partner, and thepresence of one partner's infidelity. While theconflict that occurs as a result of a growing stigmain the community, resulting in discrimination andbullying, such as harassment, humiliation, andviolence experienced that same-sex couples.Keywords: Gay, Verbal and Non VerbalCommunication, Committed Relationship. AbstrakStudi ini ingin melihat bagaimana komunikasi verbaldan non-verbal terjadi dalam jalinan ikatancommitted relationship pasangan gay, dimanaditemukan konflik internal pada pasangan bedabangsa dan konflik eksternal akibat stigma,diskriminasi dan bullying yang dipraktekkanmasyarakat. Penelitian kualitif ini dilaksanakandengan wawancara mendalam dan observasiterhadap tiga pasangan gay. Hasil studimenunjukkan bahwa untuk mempertahankanhubungan, pasangan melakukan strategi khususdalam bentuk komunikasi verbal dan non-verbalyang akan menunjukkan karakter hubunganmereka. Ikatan emosi diantara pasangan gaymenjadi alasan mereka mempertahankanhubungan intim. Konflik mereka terjadi karenakecemburuan, sikap posesif, agresif, dan danketidaksetiaan salah satu dari pasangan. Stigmadari keluarga, masyarakat bahkan negara jugamengakibatkan konflik pada pasangan karenamereka mengalami berbagai bentuk penghinaan,pelecehan maupun kekerasan.Kata kunci: Gay, Komunikasi verbal dan non-verbal,Committed Relationship